Perancangan Interior Terminal Penumpang Kapal Pesiar Di Pelabuhan Internasional Benoa, Bali - Saelendra, Irwan Nugraha (Intra, 2015)
Indonesia is the largest archipelago country in the world. In the tourism sector of Indonesia, Bali is one of the top tourist destinations. Each year tourist arrivals to the island of Bali always increases. Not often foreign travelers use cruise ships as a transportation to the island. Benoa cruise ship terminal is the only waterway entry for tourists into the island. In fact the facilities provided by Benoa cruise ship terminal inadequate for an international standard. This reason creates a necessity for passenger terminal interior design. Selected design concept is "Local Content in Modern Design" with the aim of making Benoa as an international gateway for foreign tourists who want to visit the island of Bali and to introduce Balinese local values to foreign tourists.